Report of the Working Group on Early Childhood Education and Elementary Education Set Up For Formulation of Eighth Five Year Plan - Ministry of Human Resource Development Department of Education, Government of India (Ministry of Human Resource Development Department of Education, Government of India, 1989)
The Scheme of Operation Blackboard was formulated to bring about a qualitative improvement in the Primary School system in the country. Launched during 1987-88, it aims to provide at least two all weather rooms to schools in buildings a second teacher, preferably a woman, in single teacher schools, and essential teaching and learning equipment in all primary schools in the country. This is to be done in a phased manner beginning with 20% of the blocks and municipal areas in 1987.88, 30% in 1988.89 and 50% in 1989-90.
Ministry of Human Resource Development Department of Education, Government of India
Ministry of Human Resource Development Department of Education, Government of India